(untitled) (Research, Society and Development, 2021)
This study investigated the impact of the socio-educational practices of the counselor of adolescents in conflict with the law on the establishment of medium and long-term measures for adolescents who committed an offense. This is a qualitative, descriptive-exploratory study with the collaboration of 13 adolescents, aged between 12 and 18 years old. Data were collected through a socio-familial characterization questionnaire and individual interviews with a semi-structured script. The interview script included guiding questions, which addressed the experiences lived by the adolescents during and after the fulfillment of the socio-educational measure. The results pointed to significant categories for the adolescents’ self-organization at the time of the measurement and, in this article, the focus is on the category: the relationship with the supervisor of socio-educational measurement. It was found, therefore, that for the socio-educational practices of assisted freedom to be effective and recognized by adolescents, families and society in general, it is necessary to rely on the articulation of social network work, public authorities and assiduous participation of the judiciary, in order to guarantee the basic rights of the assisted adolescent and his/her family.